Faisons la valise : le français en s'amusant. ([S.l.] : Eli, 2014)
In this entertaining French game players must pack a suitcase using all the items on a list. The game helps students learn, practice and correctly use words associated with clothing and accessories. Contains a deck of 66 photo-cards with clues and scores, an hourglass and instructions.
Bevat: 66 fotokaartjes, handleiding.
Keywords: Frans -- Basisonderwijs